Culturally Responsive Teaching as a Strategy for Strengthening the Pancasila Student Profile in Indonesian Elementary Education Teaching - Ratnasari Diah Utami; Minsih Minsih; Honest Ummi Kaltsum; Taqiya Dipsatara; Aisyara Zalzabila; Intan Putri Rahmania; Maskur Huda (STAI Hubbulwathan Duri, 2026)
This study addresses the challenges of character building within the Pancasila Student Profile (P3), particularly issues of moral degradation and cultural exclusion arising from conventional, academically oriented education systems. It aims to explore how the Culturally Responsive Teaching (CRT) approach can strengthen the six dimensions of P3 in elementary education.A qualitative case study design was employed at SD Muhammadiyah 1 Surakarta, involving six teachers and 90 students from grades IV to VI. Data were collected through participatory observation, in-depth interviews, and Focus Group Discussions (FGDs), and analyzed using the Miles and Huberman interactive model to identify patterns and themes related to CRT implementation.The findings reveal that the CRT approach significantly enhances student character development. Notable outcomes include increased collaborative engagement in ecobricks projects (Gotong Royong), improved ability to analyze phenomena grounded in local wisdom (Critical Thinking), and strengthened capacity to transform waste into functional products (Creativity). These results demonstrate that integrating sociocultural contexts into teaching fosters active, meaningful learning experiences. Furthermore, the study identifies key factors influencing implementation, including cultural relevance, teacher facilitation, and flexible instructional design.This study contributes theoretically by proposing a pedagogical model that connects the Merdeka Curriculum with local cultural realities, offering a more inclusive and context-sensitive approach to character education. Despite challenges such as limited instructional time, the flexibility of CRT integration sustains its effectiveness. Overall, the findings position CRT as a transformative framework for advancing sustainable character education in the context of globalization.